Oxygenation through oral Ox66 in a two-hit rodent model of respiratory distress - Bjorn K. Song; Danuel A. Carr; Erica D. Bruce; William H. Nugent (Artificial Cells, Nanomedicine, and Biotechnology)
Acute respiratory distress syndrome (ARDS) is a complication of pulmonary disease that produces life-threatening hypoxaemia. Despite ventilation and hyperoxic therapies, undetected hypoxia can manifest in capillary beds leading to multi-organ failure. Ox66™ is an ingestible, solid-state form of oxygen designed to supplement oxygen deficits. Twenty-four anaesthetized rats underwent a two-hit model of respiratory distress (ARDS), where a single dose (5 mg/kg) of lipopolysaccharide (LPS) was given intratracheally, and then the respiratory tidal volume was reduced by 40%. After 60 min, animals were randomized to receive Ox66™, or normal saline (NS; vehicle control) via gavage or supplemental inspired oxygen (40% FiO2). A second gavage was administered at 120 min. Cardiovascular function and blood oximetry/chemistry were measured alongside the peripheral spinotrapezius muscle’s interstitial oxygenation (PISFO2). ARDS reduced mean arterial pressure (MAP) and PISFO2 compared to baseline (BL) for all treatment groups. Treatment with Ox66 or NS did not improve MAP, but 40% FiO2 caused a rapid return to BL. PISFO2 improved after treatment with Ox66™ and 40% FiO2 and remained elevated for both groups against NS until study conclusion. Both oxygen treatments also suppressed the inflammatory response to LPS, suggesting that Ox66™ can deliver therapeutically-impactful levels of oxygen in situations of pulmonary dysfunction.